2021
DOI: 10.1186/s13071-021-04794-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four outdoor mosquito trapping methods as potential replacements for human landing catches in western Kenya

Abstract: Introduction Longitudinal monitoring of outdoor-biting malaria vector populations is becoming increasingly important in understanding the dynamics of residual malaria transmission. However, the human landing catch (HLC), the gold standard for measuring human biting rates indoors and outdoors, is costly and raises ethical concerns related to increased risk of infectious bites among collectors. Consequently, routine data on outdoor-feeding mosquito populations are usually limited because of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…funestus catch in this study reflects the predominance of anthropophagic and endophilic behaviours of the local populations as has previously been reported in the same area [ 37 , 38 ]. Other observed sources of variation include location [ 32 ], whether the traps are indoors or outdoors [ 55 , 58 ] and the presence or absence of ITNs [ 27 ]. Overgaard et al [ 55 ] observed that the results of CDC-LT efficacy may also vary based on the different statistical analyses employed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…funestus catch in this study reflects the predominance of anthropophagic and endophilic behaviours of the local populations as has previously been reported in the same area [ 37 , 38 ]. Other observed sources of variation include location [ 32 ], whether the traps are indoors or outdoors [ 55 , 58 ] and the presence or absence of ITNs [ 27 ]. Overgaard et al [ 55 ] observed that the results of CDC-LT efficacy may also vary based on the different statistical analyses employed.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of host decoy i.e. whether cow or human [ 35 ], location [ 32 , 33 ] and seasonality [ 31 ] are among the factors observed to influence the HDT performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations